The Occurrences and Formation of Ladderback Ripples on Barchans Dunes of Najaf Dunes Field, Iraq, in Aeolian Environments - Al-Naji, Ahmed Jawad; Jasim, Hasan Kattoof; Tamar-Agha, Mazin Y.; Al-Shammery, Thamer Abaas (Iraqi Journal of Science, 2021)
This paper concerns the study of ripples that occur on the windward of Barchan dunes from the dunes field of Najaf governorate, Iraq. These dunes consist mainly of sand sediments with variable sizes, including medium, fine, and very fine sands. Quartz represents the major light mineral in the Najaf Dunes sand. The prevailing wind direction in the study area is NW-SE. The major ripple crest series of every pattern are oriented perpendicular to the NW-SE wind direction, whereas imbricated ripple groups within the troughs of the preexisting ripples are created by the WSW-ENE wind trend. These ripples tend to be formed by shortened ripples that occupy the troughs of the prolonged series. All crests of the ladderback ripples are oriented at right angles to asymmetry ripples. The ladderback ripples were noticed from fine to very fine- grained sediments, which consist mainly of quartz. The wavelength of the ladderback ripples ranges from 2 – 4 cm, while they are 0.1 – 0.2 cm in height. The occurrence of ladderback ripples within an aeolian environment indicates a variety of wind directions, which influenced the arrangements of the crest ripples.